2023
DOI: 10.7150/jca.81384
|View full text |Cite
|
Sign up to set email alerts
|

High levels of baseline serum IL-10 are associated with reduced clinical benefit from first-line immune checkpoint inhibitor therapy in advanced renal cell carcinoma

Abstract: Immune checkpoint inhibitor (ICI) became a standard treatment for advanced renal cell carcinoma (RCC). However, clinically valid biomarkers of therapeutic outcome are lacking. We investigated the role of interleukin-10 (IL-10) as a predictive biomarker for first-line ICI therapy in patients with advanced RCC. Baseline serum samples were prospectively collected and analyzed using a cytometric bead assay. Patients were divided into two groups according to their serum IL-10 levels using maximally selected rank st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In contrast, studies have shown that serum IL-10 levels do not correlate with prognosis ( 27 29 ). More recently, a relationship between IL-10 and the clinical benefits of immune checkpoint inhibitors has been reported ( 30 , 31 ). The level of serum IL-10 and percentage of CD4 + IL-10 + PBMCs were associated with prognosis and treatment response in patients treated with immune checkpoint inhibitors, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies have shown that serum IL-10 levels do not correlate with prognosis ( 27 29 ). More recently, a relationship between IL-10 and the clinical benefits of immune checkpoint inhibitors has been reported ( 30 , 31 ). The level of serum IL-10 and percentage of CD4 + IL-10 + PBMCs were associated with prognosis and treatment response in patients treated with immune checkpoint inhibitors, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In general, renal cell TIME is characterized by an overwhelming abundance of immunosuppression which allows cancer cells to evade immune surveillance and cause disease progression. A preponderance of immunosuppressive cytokines such as interleukin-10 (IL-10) and transforming growth factor beta (TGF-b) promotes the differentiation of regulatory T cells (Treg) which in turn inhibit CD8+ T cells from tumor killing (19)(20)(21)(22)(23)(24)(25). In addition, tumor cells may also express PD-L1 which binds with the programmed cell death protein 1 (PD-1) on CD8+ T cells to neutralize its tumoricidal function (10,11).…”
Section: Renal Cancer Immune Environmentmentioning
confidence: 99%
“…Increased IL-10 expression in primary tumor cells and tumor-associated macrophages has been proposed as a predictor of cancer stage progression and metastatic potential development (87, 173, 174). Moreover, IL-10 circulating levels were found to be elevated in serum of various cancer patients, often accompanied by the increase of other inflammatory markers, and correlated with a poor prognosis (140,(175)(176)(177)(178)(179)(180)(181)(182)(183).…”
Section: Il-10 In Cancermentioning
confidence: 99%